Approval of variation for additional component in plumbing works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of variation for additional component in plumbing works of Brac University new campus project.